2021
DOI: 10.3390/antibiotics10101243
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Profile of Linezolid-Resistant M. tuberculosis Clinical Strains from Moscow

Abstract: Background: Linezolid, bedaquiline, and newer fluoroquinolones are currently placed as priority Group A drugs for the treatment of drug-resistant tuberculosis. The number of reported linezolid-resistant clinical strains is still low, and the correlation of molecular determinants with phenotype is not perfect. Methods: We determined the linezolid MICs for clinical isolates from the Moscow region and identified mutations in rplC and rrl genes. Results: All 16 linezolid-resistant isolates had previously reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Ribosomal protein L3 (rplC) gene mutations like C154R are prevalent. Rare rrl and rplD gene mutations have been found [128]. Linezolid is aggressively removed from bacterial cells by efflux pumps, making XDR-TB isolates resistant to it.…”
Section: Bedaquilinementioning
confidence: 99%
“…Ribosomal protein L3 (rplC) gene mutations like C154R are prevalent. Rare rrl and rplD gene mutations have been found [128]. Linezolid is aggressively removed from bacterial cells by efflux pumps, making XDR-TB isolates resistant to it.…”
Section: Bedaquilinementioning
confidence: 99%
“…The resistance mechanism for LNZ involves, primarily, mutations to ribosomal protein L3 and subunit 23S, encoded by genes rplC and rrl, respectively. The mutation C154R in RplC is one of the most prevalent ones (Ushtanit et al, 2021). Nevertheless, other mutations reported to LZD were summarized by Kadura et al (2020) and Khosravi et al (2021).…”
Section: Resistance To Other Drugsmentioning
confidence: 99%
“…As such, mutations to the 23S rRNA are also quite frequently observed in linezolid-resistant mycobacteria [ 61 ]. Mutations in the rrl gene, which encodes the 23S rRNA, have been observed in many clinical isolates, particularly g2814t, which has been reported in many locations as far apart as India, South Africa, and Russia [ 45 , 46 , 47 , 52 ].…”
Section: Mechanisms Of Linezolid Resistance In Mycobacteriamentioning
confidence: 99%
“…In a study from India, linezolid-resistant MTB was found in about 6.7% (23/343) of patients diagnosed with MDR-TB [ 46 ]. Researchers from Moscow reported the emergence of linezolid-resistant strains from TB patients undergoing treatment with Group A drugs that included linezolid [ 47 ]. In their cohort of XDR-TB patients, 6.21% (20/322) were found to have linezolid-resistant MTB.…”
Section: Introductionmentioning
confidence: 99%